Autologous Hemotherapy in Treatment of Polymorphic Eruption of Pregnancy - Martina Part (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Polymorphic eruption of pregnancy (PEP) also known as pruritic urticarial papules and plaques of pregnancy (PUPPP) is a benign inflammatory disease associated with pregnancy. The pruritic polymorphic lesions manifest in the abdominal striae with sparing of periumbilical area. Etiology of this condition is unknown. In our study, we enrolled 8 women with polymorphic eruption of pregnancy. The efficacy of different therapeutic options was assessed. The participants were randomized into two groups. Group 1 was treated conservatively with systemic corticosteroids and antihistamines until delivery and Group 2 was treated with intramuscular injections of autologous hemotherapy. In Group 1 (37,5%, n=3) the efficacy of conservative therapy was very low. The pathological skin lesions were persistent and patients suffered from serious pruritus. In Group 2 (62,5%, n=5) an intramuscular whole blood autologous hemotherapy was used in weekly intervals. Generally, pruritus improved in 2 days and skin changes disappeared in 10-15 days after starting the therapy. According to the presented results, an intramuscular autologous hemotherapy should be considered as an effective alternative therapeutic method with favorable safety profile for the mother as well as the child.